Civil Case Management in the Twenty-First Century: Court Structures Still Matter - Chan, Peter C.H; van Rhee, C.H (Ius Gentium: Comparative Perspectives on Law and Justice, 2021)
The information age provides novel tools for case management. While technology plays a crucial role, the way in which courts are structured is still critical in ensuring effective case management. The correlation between court structure and case management is a pivotal topic. The existing debate concentrates predominantly on the micro and case-specific aspects of case management, without further inquiry into the relationship between court structure, court management, and case management. The contributions within this volume fill this gap from a comparative perspective, undertaking a macro/structural and sub-macro perspective of procedure and case management